Assessing the size of non-Maori-speakers' activeMaori lexicon - Oh, Yoon Mi; Todd, Simon; Beckner, Clay; Hay, Jen; King, Jeanette (PLoS ONE, 2023)
Most non-Maori-speaking New Zealanders are regularly exposed to Maori throughout their lives without seeming to build any extensive Maori lexicon; at best, they know a small number of words which are frequently used and sometimes borrowed into English. Here, we ask how many Maori words non-Maori-speaking New Zealanders know, in two ways: how many can they identify as real Maori words, and how many can they actively define? We show that non-Maori-speaking New Zealanders can readily identify many more Maori words than they can define, and that the number of words they can reliably define is quite small. This result adds crucial support to the idea presented in earlier work that non-Maori-speaking New Zealanders have implicit form-based (proto-lexical) knowledge of many Maori words, but explicit semantic (lexical) knowledge of few. Building on this distinction, we further ask how different levels of word knowledge modulate effects of phonotactic probability on the accessing of that knowledge, across both tasks and participants. We show that participants' implicit word knowledge leads to effects of phonotactic probability-and related effects of neighbourhood density-in a word/non-word discrimination task, but not in a more explicit task that requires the active definition of words. Similarly, we show that the effects of phonotactic probability on word/non-word discrimination are strong among participants who appear to lack explicit word knowledge, as indicated by their weak discrimination performance, but absent among participants who appear to have explicit word knowledge, as indicated by their strong discrimination performance. Together, these results suggest that phonotactic probability plays its strongest roles in the absence of explicit semantic knowledge.
Keywords: Humans; Knowledge; New Zealand; Probability; Semantics